Application of Allotransplantation of Fetal Liver-derived Stem-Cells for Treatment of Type 1 Diabetes: a Single-arm, Phase 3 Clinical Trial - Ali TOOTEE; Ensieh NASLI ESFAHANI; Maryam GHODSI; Farideh RAZI; Mohammadreza AMINI; Bagher LARIJANI; Ramin HESHMAT (Tehran University of Medical Sciences, 2015)
Background: Stem-cell technology has been advocated as a potentially curative option for treatment of both type 1 and type 2 diabetes. In the current study, we aimed to assess the effectiveness of allotransplantation of fetal liver-derived cells for treatment of patients with type 1 diabetes. Methods: For the purpose of the current study, 72 patients with recently diagnosed type 1 DM were recruited and fetal liver-derived cell suspension was administered by the means of intravenous injection. Anthropometric measurements and clinical data such as body mass index, duration of the disease, daily insulin requirement were recorded as well as some of laboratory indicators of favorable therapeutic response (hemoglobin A1c, c-peptide) before and after the intention at 0, 1, 3, 6 and 12 months following the intervention. Results: Administration of fetal liver-derived fetal stem-cells resulted in significant changes in indicators of diabetes control in the patients. Required daily insulin dose and HbA1c showed significant changes, and c-peptide levels decreased significantly during the first three months of follow up period (P= 0.000) although they started the decrease after that point. Conclusion: Stem-cell therapy resulted in significant changes in indicators of diabetes control and beta-cell function. More studies are required to demonstrate effectiveness of stem-cell therapy for type 1 diabetes.   Keywords: Stem cell, Type 1 diabetes, Therapy, Iran